Between compulsions and contagions: examining the protective role of OCD against COVID-19 in a large cohort study - Avni, Chen; Sinai, Dana; Toren, Paz (Frontiers in Psychiatry, 2024)
IntroductionSince the onset of the COVID-19 pandemic in 2020, a significant body of research has explored the impact of the virus and its preventative measures on mental health among individuals with OCD. However, to our knowledge, no study has been conducted to test whether the very behaviors considered symptomatic of OCD inadvertently offer a protective shield against COVID-19 infection.MethodsThis retrospective cohort study utilized the electronic health record database of Israel’s largest healthcare provider, Clalit Health Services (CHS), to compare patients with and without recorded OCD diagnoses in terms of the number of COVID-19 tests taken, hospitalizations, vaccination rates, and infection rates during and after different pandemic waves.ResultsThe OCD group had a slightly higher rate of positive COVID-19 tests compared to the control group (p<0.001), but only since the easing of restrictions after the end of the fifth wave. The OCD group was also more likely to receive a third dose of the COVID-19 vaccine (p<0.001).DiscussionOur findings suggest that OCD may not confer protection against COVID-19 and may even be associated with slightly higher infection rates, particularly in the post-restrictions period.